Prediction of grain size in TB18 titanium alloy forgings by re-crystallization and grain growth modelling - Wei Xiang; Qineng Li; Feng Zhang; Wuhua Yuan (Materials Research Express)
After plastic deformation, metals and alloys will be in a thermodynamically unstable high free en-ergy state with a tendency to spontaneously return to a low free energy state. Understanding the laws of occurrence and development of these processes is of great significance in improving and controlling the microstructure and properties of TB18 titanium alloy. In this paper, the recrystalli-sation kinetics is investigated based on the Johnson–Mehl–Avrami equation, and a kinetic model for the grain growth of solid solution TB18 alloy undergoing predeformation at different solid solution temperatures and different solid solution times has been established by combining the Arrhenius formula and Beck’s equation to derive a prediction model for the grain size that includes three types of parameters, namely, T, t, and ε , during the solid solution process. Using simulation soft-ware(Deform) based on finite element analysis to simulate the grain size of forging heat treatment, validate the grown-up model, and analyse the deformation of each part of the forging and the grain size deviation of its corresponding position. The results show that the deviation of grain size pre-dicted by the TB18 grain size model for the forging after heat treatment is less than 10%. Overall, the size prediction model of the grain growth has been proven to be accurate and usable.